POINT PROGRAM DESIGN AND NEW CUSTOMER ACQUISITION WEB-BASED AT IBIL ASAHAN STORE - Muhammad Iqbal; Febby Madonna Yuma; Andri Nata (STMIK Royal, 2023)
Abstract: Toko IBIL Asahan is a retail business engaged in selling children's and adult clothing. Customer retention and marketing tactics are vital for corporate success. Especially for retail enterprises like the Ibil Asahan Store, it's critical to consistently create novel strategies to draw in new clients and keep existing ones. This research aims to design a web-based new customer acquisition and points program to increase buying interest and customer loyalty at IBIL Asahan stores. The research method used is a case study, which involves collecting data from primary and secondary sources. Primary data were obtained through direct observation at Toko IBIL Asahan and interviews with store management. The results of this study resulted in the design of a point program integrated with the web application to provide incentives to customers to shop regularly at Toko IBIL Asahan. This points program will give customers points every time they make a purchase, and these points can be redeemed for gifts or discounts in the future. In addition, new customer acquisition strategies are also proposed, including marketing through social media, promotional campaigns, and collaboration with local partners. This web application also provides information about point programs, special offers, and other features that can interest customers. In addition, the installation of point machines in stores will also be carried out to make it easier for customers to collect points and exchange them. Keywords: Cashier Application; database; member; point; pos Abstrak: Toko IBIL Asahan adalah sebuah usaha retail yang bergerak di bidang penjualan pakaian anak-anak dan dewasa. Strategi pemasaran dan retensi pelanggan menjadi faktor penting bagi keberhasilan bisnis. Terutama bagi bisnis ritel seperti Toko Ibil Asahan, penting untuk terus mengembangkan cara-cara baru untuk menarik pelanggan baru dan mempertahankan pelanggan yang sudah ada. Penelitian ini bertujuan untuk perancangan program poin dan akuisisi pelanggan baru berbasis web untuk meningkatkan minat beli dan loyalitas pelanggan pada toko IBIL Asahan. Metode penelitian yang digunakan adalah studi kasus, yang melibatkan pengumpulan data dari sumber primer dan sekunder. Data primer diperoleh melalui observasi langsung di toko IBIL Asahan dan wawancara dengan manajemen toko. Hasil penelitian ini menghasilkan perancangan program poin yang terintegrasi dengan aplikasi web untuk memberikan insentif kepada pelanggan untuk berbelanja secara teratur di Toko IBIL Asahan. Program poin ini akan memberikan poin kepada pelanggan setiap kali mereka melakukan pembelian, dan poin-poin ini dapat ditukarkan dengan hadiah atau diskon di masa mendatang. Selain itu, strategi akuisisi pelanggan baru juga diusulkan, termasuk pemasaran melalui media sosial, kampanye promosi, dan kolaborasi dengan mitra lokal. Aplikasi web ini juga menyediakan informasi tentang program poin, penawaran spesial, dan fitur-fitur lain yang dapat menarik minat pelanggan. Selain itu, pemasangan mesin poin di toko juga akan dilakukan untuk memudahkan pelanggan dalam mengumpulkan poin dan menukarkannya. Kata kunci: aplikasi kasir; database; member; poin; pos